PENGARUH PENGEMBANGAN KARIR, LINGKUNGAN KERJA NON FISIK, DAN EMPLOYEE ENGAGEMENT TERHADAP KEPUASAN KERJA KARYAWAN (Studi Kasus pada PT XYZ) - Muhammad Tubagus Muammar, (2022)
This study aims to determine and prove the direct and indirect effects of career development, work environment and employee engagement on job satisfaction. This research is a quantitative study with a sample of 37 employees of the HR department of PT XYZ with a sampling technique using saturated sampling technique. The analysis technique applied in this study is descriptive analysis technique and inferential analysis with the help of the SmartPLS 3.2.9 test tool. While the hypothesis test is done is t test using a significance level of 5% (0.05). The results of this study indicate (1) career development has a positive and significant effect on job satisfaction; (2) the work environment has a positive and significant effect on job satisfaction; (3) Employee engagement has a positive and significant effect on job satisfaction; (4) Career development, work environment and employee engagement variables simultaneously influence job satisfaction.